ANALISIS PENGARUH TRANSACTION COST TERHADAP HOLDING PERIOD SAHAM BIASA. - Eko Budi Santoso (Fakultas Bisnis UKDW, 2008)
The moin pwpose of this sndy is to test the effect of transaction cost totntdins period of common stock This srudy iwestigates whether investorswith longer (shorter) hwestment time horizon lold common stockswith higher (owe) bid-qsk spred as a prory of tronsaction cost. Besides,thk study also added two independent voiables such as marketvalue and variance ofrefirn-The statistical method ued in this study is two-stage least square regressionsbecause the itnestorb tnlding period md the bid-ask spreadfor each stoch are simultoteously determined. The result shows that bidask spred related positivefu ord significott to holding period. The bidask spread, morket yalue, and varianee of return have a significant Kqruords: Trqtsaction Cost, Bid-Ask Spread, Holding Period, Market Value, Variance of Return